Metacognitive Assessments for Undergraduate Mathematics Courses in the Time of COVID-19. Issue 5 (28th May 2023) - Landi, Amanda K.; Minden, Kaethe
ABSTRACT: In this paper, we assess the pedagogical approaches we employ in our US-based undergraduate mathematics courses during the COVID-19 pandemic. Our goal is to share anecdotal evidence on the use of math journals, oral exams, and learning portfolios in the synchronous online mathematics classroom. We reflect on our experience using artifacts of student materials, feedback, and dialogues.